A Financial Feasibility Study of The Train Loading System 3 (TLS 3) Capacity Upgrade Project at PT XYZ - Chico Citra Tiara; Subiakto Soekarno (CV. Ulil Albab Corp, 2026)
PT XYZ plans to increase the capacity of TLS 3 from 1.500 tons per hour to 2.500 tons per hour through conveyor motor replacement to support the company’s long-term coal production targets. This study aims to evaluate the financial feasibility of the TLS 3 capacity upgrade project, analyze the sensitivity of key variables affecting project feasibility, and formulate risk mitigation strategies by applies capital budgeting, incremental cash flow analysis, and ARIMA method for coal price forecasting. The financial feasibility analysis results indicate that the project generates a positive NPV, an IRR exceeding the WACC, a BCR greater than one, and a payback period that remains within an acceptable financial threshold. Sensitivity analysis was conducted to evaluate the impact of coal prices, fixed operating costs, variable operating costs, inflation, and CAPEX on the project’s NPV. The results visualized using spider charts and tornado diagrams indicate that coal price is the most sensitive variable affecting the project’s NPV, followed by fixed operating costs and variable operating costs. Risk mitigation strategies are recommended through operational cost control, operational efficiency improvement, preventive maintenance implementation, and periodic monitoring of coal prices and project financial assumptions. Considering the overall analysis results, the TLS 3 capacity upgrade project is considered financially feasible for implementation.